I Want to Marry *the Merchant Banker: An Exploratory Self-Paced Reading Experiment on Arab Learners’ Processing of English Articles - Мона Сабір; Алаа Мелебарі (Психолінгвістика)
Purpose. This study explores the processing of English articles by native speakers of Hejazi Arabic, a language with articles. The research aims to answer the question of whether offline (explicit) knowledge of specificity in English article choice mirrors online (implicit) knowledge. Existing research has found that Hejazi-Arabic learners of English misuse articles in the indefinite specific context when answering a written task; however, their performance is target-like in all other contexts of article use, which indicates that their production may be sensitive to specificity, similar to the production of learners from languages that do not include articles. Little has been done, though, to explore this phenomenon using online measures.